High frequency antenna design - Aditya Sunil Nalkur (2016)
This paper presents a study of using seawater as a material for a quarter wave monopole antenna for use in the High frequency range of 3-30MHz. Traditional monopoles are usually made of metals such as copper and aluminium and are excited by an electric coil. However, in this paper, the current probe is designed to be able to excite the seawater antenna stream as it passes through the monopole to transform it into an antenna for communication purposes.